The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.2307/3711225
|View full text |Cite
|
Sign up to set email alerts
|

After the Flood: The Response of Ministers to a Natural Disaster

Abstract: In this paper, we describe the roles and stresses of ministers in responding to the November, 1985, floods in West Virginia. We present the results of follow-up interviews with ministers covering such issues as work overload, frustrations, role conflict, and stress symptoms. In particular, we explore the unique challenges ministers face in helping people to integrate the traumatic and tragic events of the disaster into the theological context of their religious beliefs.Ministers often play an important role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…15,16 However, FBOs rarely are incorporated into the formal preparedness planning and response operations of government, 17 nor has their potential been recognized fully as a vital, indigenous, frontline resource for trauma-specific psychological interventions. 15,16 However, FBOs rarely are incorporated into the formal preparedness planning and response operations of government, 17 nor has their potential been recognized fully as a vital, indigenous, frontline resource for trauma-specific psychological interventions.…”
Section: Prehospital and Disaster Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…15,16 However, FBOs rarely are incorporated into the formal preparedness planning and response operations of government, 17 nor has their potential been recognized fully as a vital, indigenous, frontline resource for trauma-specific psychological interventions. 15,16 However, FBOs rarely are incorporated into the formal preparedness planning and response operations of government, 17 nor has their potential been recognized fully as a vital, indigenous, frontline resource for trauma-specific psychological interventions.…”
Section: Prehospital and Disaster Medicinementioning
confidence: 99%
“…Faith-Based Organizations— Traditionally, faith-based organizations (FBOs) have served communities admirably during and following disasters by making material resources available (e.g., food, clothing, shelter, equipment, supplies), relief personnel and by providing human services such as general fellowship, prayer leadership, and death notification 15, 16 . However, FBOs rarely are incorporated into the formal preparedness planning and response operations of government, 17 nor has their potential been recognized fully as a vital, indigenous, frontline resource for trauma-specific psychological interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Bradfield et al explained the challenges of offering hope by clergy members who were also victims. One individual said, "I wanted to share a sense of hope and to provide help, but I was feeling hopeless myself" (Bradfield et al, 1989). In addition, the authors mentioned that the clergy's personal stress levels might affect their ability to offer support.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Bradfield, Wylie, and Echterling (1989) found that hope is the key to recovery from natural disasters when they studied the collaborative efforts between clergy and mental health professionals after the floods in West Virginia in November 1985. However, they also mentioned that maintaining hope was not easy for all clergy because they themselves might be victims of the natural disaster.…”
Section: Introductionmentioning
confidence: 99%
“…There is an established body of literature discussing faith and piety following disasters. It is a common phenomenon for people to attribute natural disasters to higher powers, and for communities to seek solace within faith (Bushnell 1969;Pargament & Hahn 1986;Ahler & Tamney 1964;Bradfield, Wylie & Echterling 1989;Smith 1978;Gist and Lubin 1999;Oliver-Smith 1996;etc.). 16.…”
Section: Discussionmentioning
confidence: 99%